2004
DOI: 10.1161/01.str.0000124125.19773.40
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Perfusion Imaging in Acute Middle Cerebral Artery Infarction Predicts Outcome

Abstract: Background and Purpose-Initial reports indicate that transcranial harmonic imaging after ultrasound contrast agent bolus injection (BHI) can detect cerebral perfusion deficits in acute ischemic stroke. We evaluated parametric images of the bolus washout kinetics. Methods-Twenty-three patients with acute internal carotid artery infarction were investigated with perfusion harmonic imaging after SonoVue bolus injection Յ40 hour after the onset of symptoms. The findings were compared with those of cranial computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…US techniques are particularly useful to monitor arterial recanalization with tissue plasminogen activator (tPA) administration in acute stroke. Moreover, recent research has demonstrated the potential of transcranial color-coded sonography (TCCS) with microbubble contrast agents to assess brain perfusion [10, 11] and to identify regions of angiogenesis, inflammation and thrombus [12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…US techniques are particularly useful to monitor arterial recanalization with tissue plasminogen activator (tPA) administration in acute stroke. Moreover, recent research has demonstrated the potential of transcranial color-coded sonography (TCCS) with microbubble contrast agents to assess brain perfusion [10, 11] and to identify regions of angiogenesis, inflammation and thrombus [12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that such parameters may be suitable for assessment of the perfusion state, particularly the analysis of local time-intensity curves in prespecified regions of interest [5] or the visual interpretation of parametric images [15,16,17,18,19]. MRI and PET studies in acute stroke patients have demonstrated the diagnostic value of TPI maps for differentiation between unaffected parenchyma, penumbra, and ischemic core area [20].…”
Section: Bolus Kineticsmentioning
confidence: 99%
“…Numerous studies have documented the ability of contrast-specific ultrasound imaging to diagnose acute middle cerebral artery infarction [16, 21, 24]. Seidel et al [16] have evaluated the diagnostic and prognostic potential of bolus perfusion harmonic imaging in patients with acute middle cerebral artery infarction.…”
Section: Real-time Visualization Of Middle Cerebral Artery Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, ultrasound perfusion imaging (UPI) has emerged for the assessment of perfusion deficits in acute ischemic stroke [15,16,17] but has not yet been used in patients with primary or secondary ICH. The purpose of the present study was to evaluate this new technique to facilitate both early diagnosis and monitoring of patients with acute ICH.…”
Section: Introductionmentioning
confidence: 99%